Rickettsia typhi infection presenting as severe ARDS. (2019) - Tran, Liem T.; Helms, Jessica L.; Sierra-Hoffman, Miguel; Stevens, Mark L.; Deliz-Aguirre, Rafael; Castro-Lainez, Mirams T.; Deliz, Rafael J.
Abstract: Murine typhus, also known as endemic typhus, is a disease resulting from an infection caused by the gram-negative bacillus Rickettsia typhi . Murine typhus is identified worldwide, predominantly in tropical and subtropical geographic locations. Transmission occurs through direct inoculation by an arthropod vector, most commonly the rat flea, Xenopsylla cheopis . rickettsial infections are notorious for disseminated infections throughout the endothelial cells. The increase in permeability is an immediate consequence and has the potential of leading to non-cardiogenic pulmonary edema, otherwise known as acute respiratory distress syndrome (ARDS). Clinical manifestations are non-specific and initially mimic typical viral etiologies, obscuring early diagnosis. As a result, clinicians often do not include rickettsial infections in their differential diagnoses. Definitive diagnosis is based on clinical recognition, epidemiologic awareness, and serological testing. Here we present a confirmed case of murine typhus in a young non-immunocompromised patient who developed ARDS one week from the initial onset of symptoms.